2002
DOI: 10.1021/jm010241x
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Amino Acids for Tumor Imaging with PET:  Radiosynthesis and Biological Evaluation of 2-Amino-3-[18F]fluoro-2-methylpropanoic Acid and 3-[18F]Fluoro-2-methyl-2-(methylamino)propanoic Acid

Abstract: Novel radiopharmaceuticals, including amino acids, that target neoplasms through their altered metabolic states have shown promising results in preclinical and clinical studies. Two fluorinated analogues of alpha-aminoisobutyric acid, 2-amino-3-fluoro-2-methylpropanoic acid (FAMP) and 3-fluoro-2-methyl-2-(methylamino)propanoic acid (N-MeFAMP), have been radiolabeled with fluorine-18, characterized in amino acid uptake assays, and evaluated in vivo in normal rats and a rodent tumor model. The key steps in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 32 publications
(78 reference statements)
5
85
0
Order By: Relevance
“…Elevated uptake of [ 11 C]MeAIB into lymphoid tumors tissues in human subjects has been observed by positron emission tomography (PET) [87]. Meanwhile, the development of radiofluorinated MeAIB analogues (which are also transported by System A in 9L gliosarcoma cells) are promising agents for the detection of intracranial neoplasia via PET [61,62].…”
Section: Pathological Therapeutic and Pharmacological Considerationsmentioning
confidence: 99%
“…Elevated uptake of [ 11 C]MeAIB into lymphoid tumors tissues in human subjects has been observed by positron emission tomography (PET) [87]. Meanwhile, the development of radiofluorinated MeAIB analogues (which are also transported by System A in 9L gliosarcoma cells) are promising agents for the detection of intracranial neoplasia via PET [61,62].…”
Section: Pathological Therapeutic and Pharmacological Considerationsmentioning
confidence: 99%
“…Another limitation of both [ 11 C]AIB and [ 11 C] MeAIB is the short half-life of carbon-11 which, as in the case of [ 11 C]MET, makes widespread use of these tracers problematic. Several fluorine-18 and iodine-123 analogues of [ 11 C]AIB and [ 11 C]MeAIB have been developed, including 2-amino-3-fluoro-2-methylpropanoic acid (FAMP) and 2-methyl-3-fluoro-2-(methylamino)propanoic acid (N-MeFAMP), which show high tumor to brain ratios in the 9L gliosarcoma brain tumor model with the highest tumor to brain ratio (up to 104:1) obtained with the most selective system A substrate, N-Me[ 18 F]FAMP [185,186]. In a comparison of the enantiomers of [ 123 I]IVAIB, a radioiodinated analogue of AIB, the (S)-enantiomer demonstrated high tumor uptake as well as high tumor to brain ratios (up to 75:1) in the 9L gliosarcoma model and was primarily a system A substrate in vitro.…”
Section: αα-Dialkyl Amino Acidsmentioning
confidence: 99%
“…In our initial study with a rat brain tumor model, these fluorinated AIB/MeAIB analogs showed high and selective in vitro uptake by the system A AAT, and demonstrated excellent tumor to normal brain ratios of 20:1 to 115:1 in vivo in part due to the lack of system A transport at the normal BBB [35, 36]. To test the tumor imaging potential of these tracers for a wider range of human cancers including prostate cancer, breast cancer, and non-small cell lung cancer, we further evaluated ( R )-and ( S )- FAMP 1 and ( R )- and ( S )- MeFAMP 2 through in vitro AA uptake assays and in tumor-bearing mice implanted with human derived cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%